2008
DOI: 10.1039/b717407a
|View full text |Cite
|
Sign up to set email alerts
|

Perylene bisimide J-aggregates with absorption maxima in the NIR

Abstract: NIR absorbing J-aggregates with biomimetic features of chlorophyll dye assemblies are obtained upon hydrogen-bond directed self-assembly of a green 1,7-diamino-substituted perylene bisimide dye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…reported that the NIR azamethine dyes with an absorption maximum at 800 nm became NIR non‐absorbing permanently due to a loss of hydrogen cyanide during thermal treatment 16. Würthner et al found thermochromic perylene bisimide dyes with absorption being switched between 800 nm due to J‐aggregates at lower temperature and 644 nm due to monomeric dyes at higher temperature (90 °C) 17. Yam et.…”
Section: Methodsmentioning
confidence: 99%
“…reported that the NIR azamethine dyes with an absorption maximum at 800 nm became NIR non‐absorbing permanently due to a loss of hydrogen cyanide during thermal treatment 16. Würthner et al found thermochromic perylene bisimide dyes with absorption being switched between 800 nm due to J‐aggregates at lower temperature and 644 nm due to monomeric dyes at higher temperature (90 °C) 17. Yam et.…”
Section: Methodsmentioning
confidence: 99%
“…In order to fabricate new NIR J‐aggregated materials, rational design is required to realize the head‐to‐tail stacking. One approach is to introduce directed strong noncovalent interactions at specific positions to induce a head‐to‐tail stacking formation . Würthner and co‐workers reported a type of perylene bisimide (PBI)‐based J‐aggregate with absorption maxima in the NIR region ( Figure ).…”
Section: Fabrication Of Supramolecular J‐aggregatesmentioning
confidence: 99%
“…b) UV‐vis (black lines) and fluorescence (red line) spectra of PBI derivative in chloroform (dashed lines) and in methylcyclohexane (solid line). Reproduced with permission . Copyright 2008, Royal Society of Chemistry.…”
Section: Fabrication Of Supramolecular J‐aggregatesmentioning
confidence: 99%
“…Indeed, upon self-assembly of these PBI dyes in MCH the absorption maximum is shifted from 664 to 822 nm, i.e., by 158 nm (2900 cm −1 ). [289] …”
Section: Supramolecular Systems: Perylene Bisimide H-and J-aggregatesmentioning
confidence: 99%